Risk characterization for silica-related silicosis and lung cancer in communities adjacent to sand and gravel extraction facilities: examining limitations in our current risk methods - Russell, Anthony J.; Mundt, Kenneth A.; Maier, Andrew (Frontiers in Public Health, 2025)
IntroductionEffectively managing and reducing occupational exposure to crystalline silica continues to be a critical priority for public health agencies. The relationship between workplace inhalation exposure to respirable crystalline silica (RCS) and the onset of silicosis is well known. The body of evidence has shaped the evolution and promulgation of specific standards for the assessment and control of workplace RCS exposures. However, ongoing health effects research continues to explore the impacts of the physical and chemical forms of crystalline silica and the potential of RCS to cause lung-disease. Further, the levels at which occupational RCS exposure potentially increases the risk of lung cancer in occupational settings remains uncertain. Even less is known of the risk of lung disease associated with community level exposure to RCS. This investigation examines the implications for assessing community exposure and silicosis and lung cancer risk from: (1) direct quantitative application of occupational epidemiology data using non-threshold assumptions, and (2) application of threshold-like risk assessment approaches informed by mode of action hypotheses. An evidence integration approach is proposed with refinements to traditional methods that incorporates updates for scenario extrapolation based on the hazard quotient (HQ) approach. The approach extends the traditional application of adjustment factors in extrapolating from occupational dose–response data to include three modifying factors that address scenario-relevant data on inhalation dosimetry, exposure intensity, and relative potency of RCS forms.MethodsCommunity RCS exposures adjacent to National Sand, Stone, and Gravel Association (NSSGA) member facilities were estimated from exposure levels a forthcoming publication. The exposure levels were supplemented by publicly available data from state and federal governing bodies. Three modifying factors were hypothesized as key in determining the disease-causing potential of RCS from community exposures when extrapolating from occupational epidemiology findings. The analysis and review of the literature focused on the current research outlining each of the three factors. RCS dose-response data for lung cancer and silicosis were obtained from a recent systematic review and supplemented by web-based literature searches. Traditional risk assessment methods were applied to the epidemiological study results. For cancer risk based on linear dose–response assumptions, theoretical risk estimates for ambient and background levels of RCS were calculated using an occupational epidemiology-based regression equation. Further, traditional health-based limits derived from a point of departure and application of adjustment factors were also used to assess alignment of traditional risk assessment tools and observations regarding community risks.ResultsOccupational epidemiological studies included in the analysis were mixed, some showing a significant positive relationship between increasing silica exposure and lung cancer risk. However, other reviews have found no dose–response relationship between silica and lung cancer. In-vivo dose–response studies in animals of RCS and lung cancer were similarly limited. All studies showed increased silicosis risks above various estimated thresholds. To explore the potential difference between silicosis and lung cancer risks at the general population level, a linear regression for lung cancer risk and cumulative exposure to RCS was performed. The regression analysis resulted in a lung cancer risk = 0.069(mg/m3) X + 1.17 (p = 0.017) and a silicosis risk = 1.75 (mg/m3) X + 1.67 (p < 0.001). At the community background exposure equivalent of 4 μg/m3, these regression analyses resulted in a RR for lung cancer of 1.17 (95% CI: 1.169–1.171) and a RR for silicosis of 1.68 (95% CI: 1.66–1.69). Mode of action analyses supported a threshold-like response for lung cancer with inflammatory markers being key drivers. The upper end of the range of HQs derived by comparing the range of community exposures to health-based limits for lung effects of RCS exceeded the target value of unity. These, estimates do not align with the lack of observed effects in communities adjacent to sand, stone, and gravel operations or locations with high background levels of ambient RCS.ConclusionRisk of silicosis and lung cancer due to community exposures to RCS need to be addressed in the context of observable increases of disease in populations exposed to low to moderate levels of RCS. Direct epidemiology studies of community exposures are lacking, but no clear indication of concern based on lung effect prevalence has been reported. In the absence of such data, extrapolations for risk assessment using occupational epidemiology data as a basis for potency estimates are used and need further adjustments. Application of such adjustments would likely support a conclusion that community exposures do not exceed the threshold necessary for carcinogenesis to observe elevated levels of lung cancer or for silicosis. This analysis supports a modified HQ or modified Margin of Safety (MOS) approach with additional modifiers including inhalation dosimetry, exposure intensity and potency that address differences between occupational and community exposure scenarios.